Mitigasi Korupsi Berbasis PAR: Studi pada Bantuan Sosial Semeru Pemerintah Daerah Kabupaten Lumajang - Satria Unggul Wicaksana Prakasa; Asis Asis (Jurnal Penegakan Hukum dan Keadilan, 2023)
This study was intended to understand the pattern of mitigating corruption of social assistance (bansos) for victims of the Semeru eruption based on public awareness to escort the distribution of social assistance to residents affected by the Semeru eruption. The research employed socio-legal with a Participatory Action Research (PAR) approach, a corruption escort approach based on community solidarity. Data was collected through interviews, focus group discussions and online and offline dissemination. The results showed that (1) supervision and legal protection of the role of the community in preventing and enforcing social assistance deviations was critical. The community was vital in ensuring the country's administration ran well and was clean of corruption. (2) The participation of the general public in the administration of the state guarantees the achievement of a better Indonesia, which was still wishful. (3) The opinion of poor and marginalized communities needs to be heard due to they have the same guarantees from the constitution.